Solar energy application and its effect on microorganisms in food waste anaerobic fermentation regulated by organic load - Lei Feng; Zhipeng Liu; Xiaoyu Lin; Fangyuan Yang (Energy Reports, 2022)
Semi-continuous anaerobic digestion (AD) of food waste (FW) was conducted by solar intelligent control system to explore the impact of temperature fluctuation on microorganisms and its engineering applicability. According to analysis of the AD system at different organic loading rate (OLR), introduction of the solar intelligent control system into AD could save electric energy. Temperature fluctuation caused by climate and other factors reduced methane production by 31.79%. Before reaching the optimum OLR, the methane yield increased with the promotion of OLR and was at the optimum when OLR = 4.5 kg ⋅ m−3 ⋅ d−1. Enzyme activities changed with the change of pH. Lower pH limited the enzyme activities. At the initial stage of the reaction, Clostridium and Lactobacillus dominated, which made content of amylase and lipase reach 264.07 U/mL (solar group), 331.02 U/mL (electric group), and 276.44 U/mL (solar group), 306.75 U/mL (electric group), respectively. Temperature fluctuation brought in by the solar intelligent control system had a great effect on microbial activity. Microbial community structure was influenced by the OLR change. Methanobacterium became the main methanogenic bacterium at the middle and late stage. After analysis, it is feasible to introduce solar energy into AD.